Natural indigo toxicity for aquatic and terrestrial organisms - Natália Oliveira de Farias; Marta Siviero Guilherme Pires; Bruna de Jesus Moreira; Amanda dos Santos; Harold Stanley Freeman; Peppi Toukola; Anjaina Fernandes de Albuquerque; Riikka Räisänen; Gisela de Aragão Umbuzeiro (Ecotoxicology and Environmental Safety)
Indigo is a widely used colorant available from natural and synthetic origin. It is practically insoluble in water. Indigo can reach aquatic sediments through wastewater discharges from dyeing processes, terrestrial compartments from the treatment sludges used as biosolids and dyed textiles disposed in landfills. The aim of this work was to chemically characterize a commercial natural indigo dye from Isatis tinctoria (woad) and, evaluate its toxicity using a sediment organism (Parhyale hawaiensis) in an acute test (96 h) and the soil dwelling invertebrate Enchytraeus crypticus in a chronic assay (21 days). These organisms are model organisms and representative of the environmental compartments where dye’s destination is expected. Also, the toxicity of natural indigo was evaluated under the conditions in which it is applied to textiles. Specifically, water column invertebrate Daphnia similis was used to test indigo in its leuco form along with the salts used for its generation. The composition of the test sample was 91 % indigo, 4 % indirubin and 5 % of other components including flavonoids. The sample was toxic to P. hawaienis (LC50 309 g kg−1) and inhibited the reproduction of E. crypticus at concentrations 5.06 and 7.59 g kg−1 in dry soil. The leuco form of indigo was acutely toxic to Daphnia similis at concentrations 0.2 and 1 g L−1. The data of this study can be used to guide other indigo toxicity studies and provide information that can be used in preliminary risk assessment evaluations of environmental compartments, such as aquatic sediments and indigo contaminated soils.